KOMPETENSI PEDAGOGIK GURU SEKOLAH DASAR DALAM PEMBELAJARAN ABAD 21: MENJAWAB TANTANGAN DAN KESENJANGAN - Winursiti, Ni Made; Babang Robandi; Hairul Uyun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the challenges and gaps in the pedagogical competencies of elementary school teachers in 21st-century learning using the literature review analysis method, by examining previous research results or scientific articles published in national and international journals from 2003 to 2024. In this research, the researchers selected as many as 10 articles were analyzed and conclusions were drawn. Based on the results of the literature review, it was found that the challenges faced by teachers in creating 21st-century learning include curriculum changes, the integration of technology in learning, and the adaptation of new teaching methods or models. Meanwhile, the disparities refer to the differences in teachers' competencies between different groups in their ability to utilize technology in learning. These challenges must be faced together to create progress in the world of education, and the disparities need to be bridged to achieve equality in education.